Germplasm and Incentives for Boosting Coconut Production: Case Studies from the Pacific Region and Some Other Countries - Bourdeix , Roland; Tuivavalagi, Nat; Mataora, Victor; Jerard, Augustine B.; Hussein, Naheed (International Coconut Community, 2018)
The Coconut Industry Development for the Pacific Project (CIDP) is a joint initiative of the Pacific Community, the European Union and the African, Caribbean and Pacific Group of States. The aim of CIDP is to bolster the coconut sector in the region through improving the competitiveness of small producers and strengthening production and regional integration of related markets. In the framework of this project, CIRAD (French Agricultural Research for Development) was in charge of helping design improved seed production systems and conducting a risk analysis for coconut value chain in the Pacific region. During a meeting held in April 2018 in Fiji, thirty participants from sixteen countries and territories in the Pacific region participated to a brainstorming on incentives for boosting coconut production. In June 2018, CIRAD launched an online survey on the same topic by contacting more than a thousand of coconut stakeholders worldwide. This communication presents the first results of these two initiatives regarding incentives for boosting coconut production, in the Pacific region but also in comparison with countries from other regions.